Manajemen program Kredit Usaha Rakyat Super Mikro masa pandemi Covid-19 - Anton Adi Suryo Kusuma; Wafrotur Rohmah; Achmad Fathoni; Ahmad Muhibbin; Yulia Maftuhah Hidayati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This study aims to describe the planning, organization, implementation, and supervision of the Super Micro People's Business Credit (KUR) program during the covid-19 pandemic in BRI Unit Made, Sragen. The research method used in this research is qualitative. The research subjects were 20 people, consisting of customers, BRI managers, BRI unit heads, and BRI officers. Data collection techniques are through interviews, observations, and documents. The data validity technique used is source and technique triangulation. The results of this study reveal that in the planning stage of the Super Micro KUR program, it aims to help accelerate economic recovery during the COVID-19 pandemic by providing soft loans for entrepreneurship community capital. The strategy used is through massive socialization both online and offline. At the organizing stage in the form of division of tasks in accordance with their respective job descriptions and ensuring officers carry out their main duties and functions. The implementation phase begins with intensive socialization and marketing so that the public knows the benefits of this program. The supervision phase is carried out through daily monitoring by the unit head and BRI micro marketing manager so that credit distribution can be maximized and on target.